Takhrij and Syarah Hadith Agrotechnology Benefits of Farming - Adi Andriansyah; Wahyudin Darmalaksana; Agung Rahmadi (UIN Sunan Gunung Djati Bandung, 2021)
The purpose of this study is to discuss the hadith of the Prophet Muhammad about farming. The research method used in this research is a qualitative method through the approach of takhrij and sharah hadith agrotechnology. The results and discussion of this research are that agricultural activities have been carried out since the time of the Prophet Muhammad and are still being carried out in a more modern way. The conclusion of this research is that farming activities were highly recommended by the Prophet Muhammad from ancient times until now in a better and more sophisticated way, and this farming activity is very beneficial.